HUBUNGAN PENGETAHUAN, DUKUNGAN KELUARGA DAN PERAN PETUGAS KESEHATAN DENGAN PENERAPAN INISIASI MENYUSU DINI PADA IBU POST PARTUM DI RSUD PANYABUNGAN: HUBUNGAN PENGETAHUAN, DUKUNGAN KELUARGA DAN PERAN PETUGAS KESEHATAN DENGAN PENERAPAN INISIASI MENYUSU DINI PADA IBU POST PARTUM DI RSUD PANYABUNGAN - Dewi, Sri Sartika Sari (Jurnal Kesehatan Ilmiah Aufa Royhan, 2021)
Early Initiation of Breastfeeding (IMD) is a process let baby with his own instinct to breastfeed soon in one hour after birth, together with contact between baby's skin with mother's skin. Health worker support play a role in implementation of Early Initiation of Breastfeeding but still a lot found a health worker less supportive or motivate and does not facilitate implementation of Early Initiation of Breastfeeding at the time of delivery and not optimal commitment from health workers to apply Early Initiation of Breastfeeding in newborns. The purpose of this research To know health support relationship with the implementation of Early Initiation of Breastfeeding to maternity at Panyabungan Hospital, This Type of Research using an observational analytical survey design with a cross sectional approach.The population of this research is all spontaneous postpartum mothers at Panyabungan Hospital during the month of May to July 2021 as many as 109 people. Where is the research sample as many as 52 respondents by accidental sampling method. Statistic test results with chi square obtained p-value = 0.000 which means there is a relationship health support with Early Initiation of Breastfeeding (IMD). Conclusion There is a relationship health support on the implementation of IMD to maternity at Panyabungan Hospital in 2021. The Suggestions Results of this study can be added as reference material to add insight for health workers and postpartum mothers.